Analysis of Risk Factors for Work-related Musculoskeletal Disorders in Radiological Technologists - Kim, Taehyung (The Society of Physical Therapy Science, 2014)
[Purpose] The aim of this study was to analyze, through ergonomic analyses, those motions most used by radiological technologists that can cause musculoskeletal disorders. [Subjects and Methods] The subjects were 7 radiological technologists with work experience in hospitals for more than 5 years. For the analysis of working postures, we simulated the work posture of radiological technologists when moving patients, when pushing or pulling an apparatus, when conducting ultrasonography, and when handling a mouse for MRI were analyzed. [Results] In this study, the burdens on the radiological technologists’ waists were shown to be high when they were moving patients for a CT scan. During mouse handling for an MRI scan, large burdens were imposed on the neck. In the case of ultrasonography working postures, larger burdens on the leg and neck were found when the patient’s examination sites were located further away. The assessment of working postures when pushing a portable radiation apparatus showed that burdens on the musculoskeletal system increased as the weight of the apparatus increased. [Conclusion] The musculoskeletal disorders of radiological technologists occur in various regions of their bodies but occur most frequently in the shoulder and the lumbar region. Therefore, hospitals need to be educated regarding the concept of musculoskeletal disorders.